Innovation and Productivity in Artisan Batik Entrepreneurship: A Systematic Literature Review - Imania Nur Hidayati; Harjono, Ansell Cohen; Choirunnisa, Zuyyinna; Supriharyanti, Elisabeth; Rasjid, Taufik Hidajat; Hidayatullah, Adam Ibrahim Nur (SENTRI: Jurnal Riset Ilmiah, 2025)
The development of culture-based entrepreneurship, such as traditional batik businesses, presents both challenges and opportunities for enhancing innovation and entrepreneurial productivity. This study aims to systematically review literature related to the key factors influencing entrepreneurial performance within the context of artisan entrepreneurship, particularly among batik enterprise managers. By analyzing over 50 selected scholarly articles published within the past two decades, this review identifies the interrelation between technological opportunities, creativity, and social capital as internal resources that drive the formation of innovation capability, which in turn contributes to increased entrepreneurial productivity. The findings reveal that innovation capability functions as a crucial bridge linking technology and creativity to business performance in cultural enterprises. Furthermore, social capital plays a moderating role by strengthening the innovation process through solid community networks and the preservation of living cultural values. This study offers an integrative conceptual framework that can inform the design of empowerment strategies for batik-based UMKM and serve as a reference for future research grounded in the Resource-Based View, particularly in the development of microenterprises rooted in local wisdom.